2018
DOI: 10.1111/vsu.13126
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of patient‐specific three‐dimensional‐printed osteotomy and reduction guides for distal femoral osteotomy in dogs with medial patella luxation

Abstract: Objective: To compare precorrectional and postcorrectional femoral alignment following distal femoral osteotomy using patient-specific 3-dimensional (3D)-printed osteotomy and reduction guides in vivo and ex vivo. Study design: Prospective study. Sample population: Ten client-owned dogs and matching 3D-printed plastic bone models. Methods: Distal femoral osteotomy was performed via a standard approach using osteotomy and reduction guides developed with computer-aided design software prior to 3D-printing. Femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 32 publications
1
56
0
Order By: Relevance
“…As a complex surgery, PSG was used to achieve accurate outcome. Improvements in surgical accuracy with PSG have been reported in several case series [ 12 13 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a complex surgery, PSG was used to achieve accurate outcome. Improvements in surgical accuracy with PSG have been reported in several case series [ 12 13 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some surgical studies have reported the application of 3D plastic models as surgical guides for intraoperative use [5,6,9,17]. Moreover, the geometric accuracy of surgical guides is critical during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer-grade FDM printers have been used in some studies to produce inexpensive maxillofacial and long-bone models in an office setting [11,12]. Other studies have demonstrated that 3D-printing of patient-specific guides is a safe, promising, and affordable method that achieves satisfactory clinical outcomes [16,17]. Even though the plastic filament used in 3D printing has a low melting point, given the printed models intraoperative usage, sterilisation of plastic models using an autoclave has been suggested [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 While CT-based surgical navigation is considered the gold standard for the placement of screws in real time, there are several advantages to 3D printed guides generated from VSP when performing complex procedures such as corrective osteotomies, including development of customized cutting and reduction guides. 12,13 However, when using 3D guides, evaluation of final model accuracy can be challenging. Studies comparing outcomes of both computer-based CT-guided surgery and 3D VSP have traditionally focused on subjective outcome measures or other manual attempts at measuring angles or other proxies of accuracy.…”
Section: Introductionmentioning
confidence: 99%